Biodiversity's Stakeholders - Magnusson, William Ernest (Environmental Forum, 2020)
The whole planet depends on the improved health of the Brazilian rainforest, yet there is surprisingly little information on preserving species diversity in the Amazon. That is changing via a unique program that connects local ecosystem health with its global beneficiaries.
Keywords: Biodiversidade